Toxicological Pathologic Study of effect of various Insulin doses in mice: Buthaina.J.Jwaad ; Saleh.K.Majeed and Enaam.B.Falih - Jwaad, Buthaina J. (The Iraqi Journal of Veterinary Medicine, 2006)
This study concentrate on the effect of synthetic insulin in laboratory animals, 80 white mice, randomly divided into four main groups of males and females control –untreated, treated as low dose, intermediated dose and high dose, then every group also divided in two subgroups, the first subgroup was given Actrapid and second subgroup was given Monotrade , the tested material was given daily subcutaneously untreated control group .The injection was continued until animals were killed after 24 weeks of treatment .Clinical, macroscopical and microscopical studies of experimental mice in comparison with the control group and the result were as follows :1- Injected mice showed normal activity, with increase body weight and low food consumption in comparison to controls. On several occasions, there were attacks of hypoglycaemia with coma in treated mice.2- Macroscopic examination of treated mice showed presence of several layers of adipose tissue around visceral organs , in peri renal region , in the serosal areas of small intestine , in peri bronchial region, in subcutaneously , peri pancreatic region , splenic enlargement in scattered treated animals ,3- Histopathological changes were seen as fatty infiltration / degeneration in the liver, dilated cortical tubules in the kidney and enlarged zona fasciculate of the adrenals. In addition to atrophy and / or depletion of pancreatic islet of langerhans, also extramedullary haemopoiesis and / or atrophy of lymphoid tissue in the spleen, with peri follicular deposits of amyloid in Splenic white pulp and in glomeruli of kidneys of group B. Furthermore, there were evidence of steatitis (focal inflammation of adipose tissue) and enlargement of zona fasiculata in adrenals.